Comparative genet survival after fire in woody Mediterranean species (Oecologia, 1992)
Using data from three fires in northeastern Spain, we tested a condition necessary to support the idea that fire has been a factor in the evolution of the res- prouting habit: populations of all resprouting species within a community should show high levels of genet survival after fires and show a low coefficient of varia- tion. Species with high mean survival values were: Quer- cus ilex L., Phillyrea latifolia L., and Viburnum tinus L., with 88, 86 and 83% survival respectively; these groups had resprouts emerging from rootcrowns. Then followed Arbutus unedo L. (75%), Pistacia lentiscus L. (73 %), Erica arborea L. (77 %), Erica multiflora L. (57 %) and Juniperus oxycedrus L. (55%). This last group had resprouts from lignotnbers or burls. These two groups also differed in the variability around the mean: the first showed a lower coefficient of variation, 6-12, and the second ranged from 19 to 26. Slope exposure had no significant in- fluence on the process of resprouting, but soil depth did, with precipitation as a covariate. In the shallow soil category, the difference in genet survival between south- ern and northern exposures was 14% (71% vs. 57%); while the difference in the deep soil category was low, 5 % (87% vs. 82%). There was no significant interaction. The component of variance for soils was larger than that for species-specific effects; substantial overlap of the within- species variance indicated that species responded as if they were a single hypothetical population, in which most of the variation in chances of survival was due to the soil conditions. The possession of the resprouting habit did not ensure a high performance. Hence, we find weak support for fire as a factor in the evolution of the res- prouting habit.